DHAV-1 2A1 Peptide – A Newly Discovered Co-expression Tool That Mediates the Ribosomal “Skipping” Function - Yang, Xiaoyao; Zeng, Qiurui; Wang, Mingshu; Cheng, Anchun; Pan, Kangcheng; Zhu, Dekang; Liu, Mafeng; Jia, Renyong; Yang, Qiao; Wu, Ying; Chen, Shun; Zhao, Xinxin; et al. (Frontiers in Microbiology, 2018)
Duck hepatitis A virus 1 (DHAV-1) belongs to the genus Avihepatovirus in the family Picornaviridae. Little research has been carried out on the non-structural proteins of this virus. This study reports that 2A1 protein, the first non-structural protein on the DHAV-1 genome, has a ribosomal ‘skipping’ function mediated by a ‘-GxExNPGP-’ motif. In addition, we prove that when the sequence is extended 10aa to VP1 from the N-terminal of 2A1, the ribosome ‘skips’ completely. However, as the N-terminus of 2A is shortened, the efficiency of ribosomal ‘skipping’ reduces. When 2A1 is shortened to 10aa, it does not function. In addition, we demonstrate that N18, P19 G20 and P21 have vital roles in this function. We find that the expression of upstream and downstream proteins linked by 2A1 is different, and the expression of the upstream protein is much greater than that of the downstream protein. In addition, we demonstrate that it is the nature of 2A1 that is responsible for the expression imbalance. We also shows that the protein ‘cleavage’ is not due to RNA ‘cleavage’ or RNA transcription abnormalities, and the expressed protein level is independent of RNA transcriptional level. This study provides a systematic analysis of the activity of the DHAV-1 2A1 sequence and, therefore, adds to the 'tool-box' that can be deployed for the co-expression applications. It provides a reference for how to apply 2A1 as a co-expression tool.